Effect of Organizational Climate and Work Satisfaction on Performance of Employees in Directorate Traffic Polda Sulsel - Nuraini, Nuraini (Patria Artha Management Journal, 2018)
This study aims: (1) to analyze the influence of organizational climate on employee performance at the Directorate of Traffic of the South Sulawesi Regional Police and (2) to analyze the effect of job satisfaction on employee performance at the South Sulawesi Police Traffic Directorate.The analytical method used in this study is the Multiple Regression analysis method. The research data was obtained from the employees of the South Sulawesi Regional Police Traffic Directorate. The research approach is an explanatory causal approach.The results showed that (1) the organizational climate had a positive and significant effect on the performance of employees at the Traffic Directorate of the South Sulawesi Regional Police because good organizations were able to control the pattern of competition among employees well, and (2) job satisfaction had a positive and significant effect on employee performance. that is, if job satisfaction increases, then the employee's performance increases, and vice versa if job satisfaction decreases, then employee performance also decreases